Outward Migration to ASEAN Economic Community: A Study of Thai IT Professionals - Theerataweewut, Yingyos; Popaitoon, Patchara; Kongchan, Ananchai (NIDA Development Journal, 2018)
This research explores the extent to which Thai IT professionals are interested to work in the member states of ASEAN economic community (AEC) and factors influencing them to work in these countries. Our sample is Thai IT professionals in private organizations and we use non-probability sampling techniques to attain 453 respondents participating in our online survey. Results show that Thai IT professionals have moderate to high interest to work in AEC. Self-efficacy in working abroad and career growth expectation are the two key factors influencing Thai IT professionals’ interest to work in ASEAN countries. In contrast, English language proficiency, marital status and family influence are not significantly associated with Thai IT professionals’ interest to work in these countries. This suggests that Thai IT professionals especially those who have high self-efficacy in working abroad and expect career growth opportunity would be interested to work in the member states of AEC once a free flow of workforce mobility is made possible. Therefore, management should apply career development opportunity as the means to attract and retain IT professionals.